Implementasi Program Tahfidz Al-Qur'an di Sekolah Dasar Islam Terpadu (SD IT) Cahaya Hati Pauh Kambar Padang Pariaman - Irfanita, Irfanita; Murniyetti, Murniyetti (Lembaga Yasin AlSys, 2023)
The background of this research is the growing development of the implementation of the Tahfidz Al-Qur'an program in various schools, both formal and non-formal schools with various strategies, methods and techniques carried out to ground the Al-Quran. This study aims (1) to determine the planning of the Tahfidz Al-Qur'an program at SD IT Cahaya Hati Pauh Kambar, (2) to analyze the implementation of the Tahfidz Al-Qur'an program at SD IT Cahaya Hati Pauh Kambar, (3) to find out the evaluation of the Tahfidz Al-Qur'an program at SD IT Cahaya Hati Pauh Kambar. This research uses descriptive qualitative method. The objects of this study were students and teachers of Tahfidz Al-Qur'an at the Integrated Islamic Elementary School (SD IT) Cahaya Hati Pauh Kambar Padang Pariaman. The subject of this research is the application and implementation of the Tahfidz Al-Qur'an program with data obtained from observations, interviews with informants, and documentation. The results of this study indicate that first, the planning of the Tahfidz Al-Qur'an program at SD IT Cahaya Hati Pauh Kambar was carried out quite well. The aim of Tahfidz Al-Qur'an is to produce generations of Al-Qur'an lovers. The target of this program is that students have memorized at least 3 chapters (juz 30, 29 and 1). Second, the implementation of the Tahfidz Al-Qur'an program at SD IT Cahaya Hati Pauh Kambar for low grades and high grades has different times, methods, and implementation. For lower grades, the methods usually used are the talaqqi method, the method of connecting verses between students and memorizing muroja'ah. As for the high class, they are more likely to use the talaqqi, taqrir, sima'an taakhi (muroja'ah with friends) methods and learn recitations of the Qur'an. Third, the evaluation of the Tahfidz Al-Qur'an program at SD IT Cahaya Hati Pauh Kambar is carried out in a meeting once a month to measure how far the targets and goals have been achieved by students.